1997
DOI: 10.1016/s0022-5347(01)65196-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bone Metabolic Markers and Bone Scan in Prostatic Cancer

Abstract: Pyridinoline cross-linked carboxyterminal telopeptide might assist PSA and bone scintigraphy in monitoring metastatic bone activity of prostatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 15 publications
0
24
1
2
Order By: Relevance
“…36 These markers can be used to guide decision making regarding the treatment of metastatic bone disease when the marker levels are elevated in patients with abnormal bone scans. [32][33][34] Whether the markers can be used to determine early bone involvement or micrometastases before the bone scan turns positive in high risk cancer patients still remains to be determined. [32][33][34] Whether the markers can be used to determine early bone involvement or micrometastases before the bone scan turns positive in high risk cancer patients still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…36 These markers can be used to guide decision making regarding the treatment of metastatic bone disease when the marker levels are elevated in patients with abnormal bone scans. [32][33][34] Whether the markers can be used to determine early bone involvement or micrometastases before the bone scan turns positive in high risk cancer patients still remains to be determined. [32][33][34] Whether the markers can be used to determine early bone involvement or micrometastases before the bone scan turns positive in high risk cancer patients still remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the lytic component is obvious in that anti-resorption medicines, bisphosphonate and anti-RANKL monoclonal antibody, are used to treat skeletal metastases of prostate cancer [16, 17]. We formerly reported that both formation and resorption markers increased in prostate cancer patients with skeletal metastasis [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Markers of bone resorption, such as urine N-telopeptide (NTx) and bone-specific alkaline phosphatase, are higher in patients with bone metastasis compared to those without, indicative of elevated bone turnover despite the osteoblastic radiographic appearance[18, 19]. Increased osteoclast activity is independently associated with risk for subsequent skeletal complications, disease progression, and death[5, 20].…”
Section: Pathophysiology Of Bone Metastasis From Prostate Cancermentioning
confidence: 99%